Fred Lindsey. - Unknown:::Creator::::::::::::
Fred Lindsey, San Jose State football player that participated as part of the Honolulu Police Department right after the attack of December 7th on Pearl Harbor. Fred Lindsey decided to stay as part of the Honolulu police force rather than come back to San Jose with the rest of the team; he stayed five years.